Specular microscopy findings in diabetic patients: a systematic review and meta-analysis - Ali Sharifi; Amir Masoud Moeini; Mohsen Nabi-Afjadi (Clinical Diabetes and Endocrinology)
Abstract Objective To evaluate the specular microscopy findings in patients with diabetes mellitus (DM) through a systematic review and meta-analysis. Methods A systematic search with the appropriate keyword was done in the online databases including PubMed, Scopus, and Web of Sciences. The records were imported into EndNote software and duplicated records were removed. The title, abstract, and full text of the articles were evaluated carefully. STATA software also was used for all data analyses. The mean difference (MD) and 95% confidence intervals (95% CIs) were used to examine the data. Results After a systematic search, 781 records were evaluated and finally, 14 of them were selected for final analysis. The results showed that the mean differences in average cell size (MD = 21.22, 95% CI 10.43, 32.01, P 0.001), central corneal thickness (MD = 9.90, 95% CI 6.07, 13.73, P 0.001), and coefficient of variation (MD = 1.11, 95% CI 0.11, 2.11, P = 0.03) were higher in diabetic patients in comparison with healthy cases. However, the mean differences in endothelial cell density (MD = -114.29, 95% CI -158.34, -70.24, P 0.001) and hexagonal cell ratio (MD = -3.52, 95% CI -5.79, -1.25, P < 0.001) were lower in diabetic cases. Conclusions Patients with DM have higher average cell size, corneal thickness, and coefficient of variation. On the other hand, the endothelial cell density and hexagonal cell ratio were reduced in diabetic cases.